Outcomes of microvascular composite reconstruction for mandibular osteoradionecrosis. Issue 9 (November 2021) - O'Connell, J.E.; Brown, J.S.; Rogers, S.N.; Bekiroglu, F.; Schache, A.; Shaw, R.J.
Abstract: The aim of this retrospective study was to compare outcomes and reconstruction-related complications in patients receiving a composite free flap reconstruction of the mandible for ORN with those reconstructed for other indications. The records of all patients who underwent composite reconstruction of a mandibular defect at Aintree University Hospital, Liverpool, were reviewed and analysed. Based on radiotherapy exposure and ORN history, the study cohort was divided into three separate case-matched groups. Local wound healing issues were markedly more common in the ORN setting, as was infection and subsequent osteosynthesis plate(s) removal. Free flap survival was similar among all three case-matched groups. Advanced mandibular ORN may be safely and predictably reconstructed with composite free flaps, and that while the rate of local complications is greater than non-irradiated, and non-ORN case-matched controls, the free flap survival rate compares favourably.